ANALYSIS OF ARTICLE 21 INCOME TAX CALCULATIONS AND DEDUCTIONS ON EMPLOYEE SALARIES AT PT BTx - Kevin Julian Depthios; Anjaling Anjaling; Dian Aprilia Eleuwarin; Dion Alpandy S.S; Afian Dezi Sanda Sipi (SEAN Institute, 2023)
This study entitled